Mental health enrollment in primary care: An integrative literature review (Research, Society and Development, 2021)
Matricization appears as a new model to produce health, causing two or more teams to develop a pedagogical-therapeutic intervention proposal, in a shared construction method. The objective of this study is to know the evidences in the literature of the last 06 years regarding mental health enrollment in primary care, as well as its benefits and possible difficulties of implantation. This is a descriptive study, with a qualitative approach and an exploratory nature, of the Integrative Literature Review (RIL) type. The databases used were BDENF, LILACS and SCIELO. After applying the inclusion and exclusion criteria, of the 37 results in the electronic databases, a sample of 15 studies was obtained. From the analysis of the articles, two categories were identified, chosen by clusters of approximation of contexts and ideas: 1) benefits and results of the matrix model; 2) factors that interfere in the implementation of the matrix. It was found that most of the studies reported the contributions of the implementation of the matrix model in mental health. However, the lack of technical training, stigmata and prejudices, as well as the centralization and bureaucratization of services make it difficult to adhere to this strategy.